EXPLORING PROSPECTS OF WEB-PUBLISHED ACADEMIC ENGLISH COURSEBOOK FOR NON-ENGLISH MAJOR STUDENTS - Abdullah, Muhaimin; Sampelolo, Rigel; Syawal, Syawal; Wanci, Risman (Institut Agama Islam Negeri (IAIN) Bone, 2023)
This study explores opportunities for web-published academic English coursebook to be applied as primary learning resource for non-English major students in Indonesia. Large scale social restriction due to Covid-19 pandemic that disallows regular face to face meeting to be conducted and the fact that English coursebook has not been developed yet at locus of the study lead the authors to set this phenomenon as important and urgent. The data were gathered from a total of 68 non-English major students at a state university in Makassar, Sulawesi Selatan, Indonesia. Data were obtained through interview, observation, and document analysis. This publication entails on (1) the perceived importance and the urgency of academic English coursebook; (2) participants’ internet self-efficacy; and (3) participants’ perception on faculty readiness in terms of infrastructures. This study contributes to English as a foreign/second language domain that it sheds light on how to begin the design and development of web-oriented academic English coursebook for non-English major students.